Barriers and drivers of sustainable hotel implementation: A systematic review - Salsabila Shafia Dyaninta; Sinta Rahmawidya Sulistyo; Yun Prihantina Mulyani (OPSI, 2026)
Sustainability is becoming progressively important in the hospitality industry, especially in the implementation of sustainable practices in hotels. This study is a systematic literature review (SLR) that aims to explore the barriers and drivers of sustainable hotel implementation across four key pillars: economic, social, environmental, and cultural. The paper synthesizes existing studies from 2020 to 2026 to identify factors that hinder and promote sustainability in hotels. Barriers include financial constraints, lack of awareness, and complex regulations, while drivers such as cost savings, improved guest experiences, and government incentives play significant roles. The analysis suggested potential strategies to help hotels navigate these barriers and utilize key drivers to reach sustainability. The mapping of potential strategies highlights the need for integrated policies, employee training, and technology investments. The study demonstrates that stakeholder engagement in facing challenges is key to the successful implementation of sustainability in hotels. The implications of this research are essential for guiding hotel management, policymakers, and society in building and supporting sustainable practices within the hospitality industry.